2019
DOI: 10.1021/acsanm.9b02174
|View full text |Cite
|
Sign up to set email alerts
|

{Mo72Fe30} Nanoclusters for the Visible-Light-Driven Photocatalytic Degradation of Organic Dyes

Abstract: The photocatalytic efficiency of ecofriendly Keplerate {Mo72Fe30} nanoclusters in degradation of hazardous organic dyes such as rhodamine B (RhB) under visible/solar light is exploited. A higher photoremoval activity was observed for amorphous {Mo72Fe30} than its crystalline counterparts and other Keplerates. The greater specific surface area (SBET) and, particularly, pore volume (V BJH) of the amorphous {Mo72Fe30} cluster than those of its rhombohedral crystal (3- and 28-fold for SBET and V BJH, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…The unit cell results in large number of reflections whose separation is less than the resolving power of the diffractometer at Cu−Kα wavelength [51] . The PXRD pattern recorded for the old sample is similar to those reported for the crystalline {Mo 72 Fe 30 } [52] …”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…The unit cell results in large number of reflections whose separation is less than the resolving power of the diffractometer at Cu−Kα wavelength [51] . The PXRD pattern recorded for the old sample is similar to those reported for the crystalline {Mo 72 Fe 30 } [52] …”
Section: Figuresupporting
confidence: 71%
“…[51] The PXRD pattern recorded for the old sample is similar to those reported for the crystalline {Mo 72 Fe 30 }. [52] The dynamic vapour sorption analysis for Keplerate 1 was performed at 25°C as shown in Figure 6. From the given figure, it can be seen that as the relative humidity is increased monotonically, the sample shows a linear response in terms of the amount of water vapor uptake.…”
mentioning
confidence: 99%
“…It is recognized that the growth of photocatalysis, especially for the abatement or removal of organic pollutants from wastewater, is of great significance for environmental protection. In recent decades, much focus has been placed on the application of POMs and related composites in the photocatalytic degradation of organic dyes. RhB and MB are representative organic dye contaminants, and therefore, these two dyes are harnessed to demonstrate the photocatalytic properties of compounds 1 and 2 under UV irradiation; see Figures S21 and S22. Photocatalytic experiments revealed that compounds 1 and 2 displayed 91.28% and 92.58% RhB degradation efficiency (1 – C t / C 0 ) (where C t is the concentration of the dye after the photocatalytic degradation has proceeded for a certain period of time, and C 0 is the initial concentration of the dye before the photocatalytic degradation) after 150 min, respectively (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…A fluorescent 40 W lamp was utilized as an artificial visible radiation source equipped with cut-off filters: a solution mixture of KMnO 4 , MB (methylene blue) and phenol red to irradiate at λ ≈ 760 nm with lux = 1093; 24 a mixture of KMnO 4 , Cu(NO 3 ) 2 and KCrO 4 to illuminate at λ ≈ 600 nm with lux = 4895; a green filter (Leybold Heraeus GmbH 46807) to illuminate at λ ≈ 530 nm with lux = 7145; a blue filter (Leybold Heraeus GmbH 46811) to illuminate at λ ≈ 450 nm with lux = 5773; and a solution of MB to irradiate at λ ≈ 415 nm with lux = 2786 were used as filters in this research. The reduction of Cr( vi ) was accomplished based on the aforementioned method.…”
Section: Methodsmentioning
confidence: 99%